Management of Heart Failure Volume 1: Medical - Pitt, Bertram; Givertz, Michael; Baliga, Ragavendra (Springer London : Imprint: Springer, 2008)
Management of Heart Failure has been conceived as a rapid but comprehensive review for practitioners of all persuasions involved in the management of patients with heart failure. Heart failure is a problem of epidemic proportions in all parts of the world. State of the art treatment may not be accessible to all, but simply creating an awareness of simple methods of diagnosis and treatment would assist in promoting a better global response to this epidemic. This practical volume, written by a panel of world-renown cardiology experts, focuses on the medical management of heart failure and outlines the causes, etiopathology and mechanisms in such a way that most health care professionals can grasp the concepts. The book details the common investigations, clinical profiles and therapeutic paths required of all clinicians with these patients under their care. This volume will be essential reading for all specialists dealing with patients with or who are at risk of heart failure, including but not limited to cardiologists, emergency medicine physicians, critical care physicians, interventionalists and cardiac surgeons.